Bridging Gaps, Building Trust: Comparative Insights into Community Engagement for Public Service Innovation in Makassar City and Sinjay Regency - Haerana, Haerana; Fatmawati, Fatmawati; Lail, Hijrah (Jurnal Studi Pemerintahan, 2024)
This research aims to explore the level of community participation in public service innovation and explore the factors supporting this innovation. This type of research uses a mixed method, where in this type of quantitative research, the quantitative method used is cross-sectional with convenience sampling techniques, while qualitative research uses interview and observation data collection methods and is analyzed using Nvivo 12 Plus software. The results of the research show that the level of community participation in Makassar City is that the level of decision making is at the "not good" level because it is only around 38%, whereas at the implementation stage with a value of around 78% and the evaluation with a value of around 76% can be categorized as "Good" and in the category "Very Good" is only at the innovation utilization stage, namely reaching a percentage value of around 88%. Meanwhile, in Sinjai Regency, the very good category is only in the aspect of utilizing innovation, namely around 83%. Meanwhile, the aspects in the good category are implementation and evaluation indicators with respective percentage levels of 78% and 63%. The lowest level of community participation was in the decision-making aspect, namely with a percentage of around 55% in the "sufficient" category. The research results relate to supporting factors for participation, namely the will of the community, knowledge, awareness of implementing government programs, benefits of innovation, innovation systems and togetherness in the community. Meanwhile, the inhibiting factors are the lack of community involvement in determining government policy, community perception, busy work, weak program outreach. Thus, regional governments are expected to continue to increase community participation, especially in the decision-making aspect.